Azad’s Scheme of Composite Nationalism: Content and Logic - Misbah Umar (JSSH, 2023)
The paper evaluates the concept of composite nationalism with special reference to Maulana Abul Kalam Azad, an intrepid politician and eloquent intellectual. Azad’s scheme of composite nationalism was against the Muslim League’s popular demand of separate homeland for Muslims. The scheme of composite nationalism by Azad incorporated the themes of anti-imperialism, pan-Islamism and anti- communalism. These aspects of composite nationalism overlap and intertwine each other in terms of inception, development and manifestation.